The prevalence of hepatitis - B and C serological markers among patients with thalassaemia in Mosul - Bashar Sh. Mustafa (University of Mosul, 2010)
Background: Thalassaemic patients are known to have higher risk of developing hepatitis B and C than normal individuals .The aim of this paper is to determine the prevalence of hepatitis B and C among thalassaemic patients and to pinpoint its association with personal medical fators in the province of Mosul. Methods: From August 2003 to March 2004 ,626 patients under the age of 20 years with thalassaemia were surveyed and screened for hepatitis HBs Ag and anti-HC Antibody (Ab) in the Thalassaemia Center in Ibn AL-Atheer Children Hospital in Mosul . Results: 5.59% of the patients have positive HBs Ag (1.92% have combined hepatitis B and C), 28.12% have anti HC-Ab. The prevalence of hepatitis B and C was higher in patients older than 15 years. Conclusion: Viral hepatitis is prevalent in thalassaemic patients in Mosul. Seropositivity is significantly related to age, vaccination, family history of hepatitis, history of splenectomy; number of blood transfusion per year,and severity of thalassaemia.